Pengendalian Throughput Pabrik Kelapa Sawit Menggunakan Individual Moving Range (I-MR) Chart - St Nugroho Kristono; M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
This research discusses the control of throughput in a palm oil mill (POM). The purpose is to find out how the POM throughput conditions and how the losses due to these conditions. This research uses the individual moving range (I-MR) Chart method. Testing is done first with MR-Chart, and revisions will be made if there is an out-of-control condition. Next, testing of throughput conditions with x-Chart will be conducted. If an out-of-control condition occurs, a process capability measurement (Cp) will be carried out. The result showed that the POM studied had poor throughput conditions. To make the existing conditions seem good or very good, tolerance is needed that is beyond the limit of reasonableness. This condition resulted in considerable losses for the company because it had to spend operational cost because there were additional operating hours that should not have happened, even though there were no FFB processed during these additional hours.